GAYA KEPEMIMPINAN DEMOKRATIS KEPALA DESA DALAM PELAKSANAAN PEMBANGUNAN DI DESA GEMPOLSARI - Laila Ihza Masithah; Isnaini Rodiyah (Halu Oleo University, 2024)
As part of the Indonesian government’s strategy to achive equitable welfare, sustainable development is a primary focus, as stipulated in Law Number 25 of 2004 concerning the national development planning system. This research analyzes the application of the democratic leadership style by the village chief in the implementation of the development in Gempolsari village. With a descriptive and qualitative approach, this study aims to analyze and describe the democratic leadership style of village chiefs through decision-making abilities, motivational skills, communication skills, the capacity to manage subordinates, and emotional control in the implementation of development. The research methods include observation, interviews, and documentation, with data analyzed using the Miles and Huberman analysis model. Research findings indicate that the democratic leadership style of the Village Chief is a crucial aspect in the implementation of development by involving the community in decision-making through deliberation, motivating employees and managing subordinates and emotions also affects the smoothness and success of the development implementation.